Benzopyrans from Curvularia sp., an endophytic fungus associated with Ocotea corymbosa (Lauraceae) - Teles, Helder Lopes [UNESP]; Araújo, Ângela Regina [UNESP]; Silva, Geraldo Humberto [UNESP]; Castro-Gamboa, Ian [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Pereira, José Odair; Costa-Neto, Claudio Miguel; Haddad, Renato; Eberlin, Marcos Nogueira; Young, Maria Claudia Marx (Elsevier, 2005)
An isolate of Curvularia sp. was obtained from the leaves of Ocotea corymbosa, a native plant of the Brazilian Cerrado. The ethyl acetate extract from culture of this fungus afforded two benzopyran derivatives: (2′S)-2-(propan-2′-ol)-5-hydroxy-benzopyran-4-one (2) and 2,3-dihydro-2-methyl-benzopyran-4,5-diol (4); and two known benzopyrans: 2-methyl-5-methoxy-benzopyran-4-one (1) and (2R)-2,3-dihydro-2-methyl-5-methoxy- benzopyran-4-one (3). The structures of 2 and 4 were established on the basis of comprehensive spectroscopic analysis, mainly using 1D and 2D NMR experiments. The benzopyrans 1 and 2 showed weak in vitro antifungal activity against Cladosporium sphaerospermum and C. cladosporioides. Analyses of the biological activities were also carried out on HeLa (human cervix tumor) and CHO (Chinese hamster ovary) cells, aiming to evaluate their potential effects on mammalian cell line proliferation. Results from both cell lines indicated that compound 2 was able to induce cell proliferation: 70% on HeLa cells and 25% on CHO cells. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Benzopyrans; Cell proliferation; Curvularia; Endophytic fungi; Metabolites; antifungal agent; antineoplastic agent; benzopyran derivative; animal; Ascomycetes; cell proliferation; cell survival; chemical structure; chemistry; Cricetulus; drug effect; drug screening; growth, development and aging; hamster; human; isolation and purification; microbiology; Ocotea; tumor cell line; Animals; Antifungal Agents; Antineoplastic Agents; Ascomycota; Cell Line, Tumor; Cell Proliferation; Cell Survival; Cricetinae; Drug Screening Assays, Antitumor; Humans; Molecular Structure; Cladosporium; Cladosporium cladosporioides; Cladosporium sphaerospermum; Cricetulus griseus; Fungi; Lauraceae; Magnoliophyta; Mammalia; Ocotea corymbosa